2013
DOI: 10.1073/pnas.1207458110
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling in chondrocytes modulates endochondral ossification and osteoarthritis development

Abstract: Here we examined the involvement of Notch signaling in the endochondral ossification process, which is crucial for osteoarthritis (OA) development. Intracellular domains of Notch1 and -2 were translocated into the nucleus of chondrocytes with their differentiation in mouse limb cartilage and in mouse and human OA articular cartilage. A tissue-specific inactivation of the Notch transcriptional effector recombination signal binding protein for Ig kappa J (RBPjκ) in chondroprogenitor cells of SRY-box containing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
170
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(178 citation statements)
references
References 44 publications
8
170
0
Order By: Relevance
“…Furthermore, Notch pathway is highly activated in mouse and human joint tissue during post‐traumatic OA. Sustained Notch activation in adult joint cartilage contributes to a severe, early, and progressive OA‐like pathology (Hosaka et al., 2013; Liu et al., 2015), while temporary suppression of Notch signaling leads to the delayed progression of OA in murine joints (Hosaka et al., 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Notch pathway is highly activated in mouse and human joint tissue during post‐traumatic OA. Sustained Notch activation in adult joint cartilage contributes to a severe, early, and progressive OA‐like pathology (Hosaka et al., 2013; Liu et al., 2015), while temporary suppression of Notch signaling leads to the delayed progression of OA in murine joints (Hosaka et al., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Left knee joints were left intact and are termed “left unoperated control joints” (Botter et al., 2009; Glasson, Blanchet & Morris, 2007). For each intra‐articular administration of DAPT in miR‐146a −/− mice (Hosaka et al., 2013), we injected 5 μl of 5 μ m DAPT solution, which was prepared by diluting 50 m m DAPT in dimethyl sulfoxide (DMSO) with injectable normal saline at 1:10,000, and 10 μl of DMSO diluted with normal saline (1:10,000) as the control. We performed intra‐articular administration of DAPT right after surgery and then once a week for 7 weeks after the surgical induction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, one of the studies showed a cooperation of Notch and transforming growth factor ␤ (TGF-␤) signaling pathways in the process (39). As both MMP-1 and MMP-13 expression levels are known to be regulated by TGF-␤-induced signals (40) and Notch signaling has been shown to affect MMP-13 expression (41,42), it is possible that SLFN5 controls MMP-1 and MMP-13 expression, as well as cell motility and invasion through its effects on NOTCH/TGF-␤ signaling. Expression of MMPs can also be modulated by additional pathways (43).…”
Section: Discussionmentioning
confidence: 99%
“…AOS is an autosomal dominant disorder caused by mutations in RBPJ and/or NOTCH1 genes resulting in Notch LOF, although no additional molecular mechanisms underlying this disease are known (Hassed et al, 2012;Stittrich et al, 2014). Notch signaling defects, either GOF or LOF, have also been implicated in osteoarthritis (Mahjoub et al, 2012;Hosaka et al, 2013;Mirando et al, 2013;Sassi et al, 2014;Liu et al, 2015), rheumatoid arthritis (Nakazawa et al, 2001;Park et al, 2015) and osteoporosis (Engin et al, 2008;Hilton et al, 2008;Majewski et al, 2011;Simpson et al, 2011), and have been associated with a predisposition to pathologic fractures (Kung et al, 2010). Studies like the one presented here further our understanding of the molecular players and events that Notch signaling might control during normal skeletal development, as well as our understanding of how they contribute to the pathology of certain skeletal diseases and injury processes.…”
Section: Discussionmentioning
confidence: 99%